Mediating role of Digital Ethics on the impact of Artificial Intelligence Usage and Public Relations Practices: evidence from Malaysia - Khalid, Umaima; Ahmad, Mokhtarrudin; Chan, Tak Jie; Pradana, Mahir; Singh, Satnam (Frontiers in Artificial Intelligence, 2025)
The use of Artificial Intelligence (AI) has led to great advancement in the field of Public Relations (PR); however, the organisations are still unsure about the ethical consequences of this new technology. This study aims to examine the effect of AI usage on PR practices by examining the mediating role of Digital Ethics. The study used a cross-sectional quantitative method. The data was collected through structured survey questionnaires from PR practitioners in a Malaysian setting. Mediation analysis was run using the Statistical Package for Social Sciences (SPSS) and PROCESS macro-Model 4. The results showcased that AI usage has a significant impact on PR practices, while Digital Ethics further mediates the relationship, suggesting that AI, when employed ethically, assists in efficient PR practices. This work fills a critical gap in the literature regarding the role of Digital Ethics in the landscape of AI usage for performing PR activities. The study extends the Excellence Theory scholarship into an AI-driven ethical context. The findings offer a crucial incentive for organisations to introduce robust ethical guidelines into their AI-driven PR strategies. The study suggests that by being aware and readily employing Digital Ethical practices, PR practitioners can not only increase their productivity but also safeguard their organisations against the potential ethical threats posed by AI.